Development and Validation of Educational Video Tutorials for 21st Century Secondary Learners - Acedo, Ederlina; Robles, Ava Clare Marie O (Asian Journal of Multidisciplinary Studies, 2019)
Amidst the proliferation of various technological advancements, achieving proficiency in solving problems that require higher thinking skills is still a common problem in public secondary schools. One of the platforms to address this needs is through the utilization of educational video tutorials that were validated correctly by experts before these were hand-me-down to the consumption of the public high school students. This study used the Research and Development (R and D) design. The skills included in the video tutorials were identified using the K-12 Curriculum Guide. The developed video tutorials underwent validations from forty-five (45) experts. Based on the evaluation ratings, the video tutorials were highly acceptable and highly relevant. Likewise, the videos were also considered as highly appropriate and usable. This finding showed that the developed videos were acceptable to a great extent. Hence, it can be concluded that these video materials were substantial, which may help improve students' computation skills. Therefore, the developed video tutorials may be used as instructional materials, remediation, and enhancement activities of the 21st teachers here or abroad.